Frailty research : a scoping review utilising a topic modelling approach - Wah, Alvin Chin Yang (2018)
The global ageing population phenomenon is a key issue for many developed countries. Due to associations with ageing, interest in frailty has been growing. It is becoming increasingly difficult for researchers to be in sync with the growing knowledge pool. To aid in research synthesis efforts, the present study adopted a topic modelling approach to carry out a scoping review. The two objectives of the study are to identify terms related to frailty and to depict the transformation of frailty research focus. A search for frailty literature was done on the Web of Science database and the search returned a total of 8,148 bibliographical records. After executing the topic modelling process on R Studio, a total of 114 topics was deemed to be optimal. The topics were analysed, and 107 themes were identified. An analysis was also done on the generated terms associated with the topics. 450 suggested terms were derived and categorised into eight categories, namely Population/Settings, Conditions/Issues, Modality, Research Methodology/Assessments, Physiology, Anatomy, Constructs/Philosophy and Others. After which, the literature in the top ten themes were plotted against the years in which they were published. Several interesting trends were discovered. Terms that associated with preventive community-based modalities, cognitive and social frailty were discovered, seen as emerging themes and possibly signal a switch in research focus. With this information, scholars will be better informed on the landscape of frailty research. Through the above three analyses, a panoptic view of frailty research is presented.